1989
DOI: 10.1089/aid.1989.5.663
|View full text |Cite
|
Sign up to set email alerts
|

Lymphotoxin cDNA Clones from a HTLV-I-Carrying T Cell Line HUT-102

Abstract: The conditioned medium of a HTLV-I-carrying T cell line HUT-102 showed cytotoxic activity against a mouse fibroblast cell line L-M. We prepared the cDNA library from HUT-102 poly(A)+ RNA and screened it using oligonucleotide probes that correspond to the amino acid sequences conserved in tumor necrosis factor (TNF) and lymphotoxin (LT). As a result we obtained two kinds of cDNA clones encoding LT in which amino acid residue 26t of mature LT is different; one is Asn and another is Thr. The sequence of the genom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
4
0

Year Published

1990
1990
1999
1999

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…2), as a previously reported polymorphism in the 3' untranslated region was described with a frequency of 6% (25) . No homozygous 2.5-kb EcoRI sub- Figure (10,34,36) or contain in exchange ACC = Thr at amino acid position 26 (9, 35,36). We wondered whether the NcoI RFLP is linked with the presence of AAC at amino acid position 26.…”
mentioning
confidence: 99%
“…2), as a previously reported polymorphism in the 3' untranslated region was described with a frequency of 6% (25) . No homozygous 2.5-kb EcoRI sub- Figure (10,34,36) or contain in exchange ACC = Thr at amino acid position 26 (9, 35,36). We wondered whether the NcoI RFLP is linked with the presence of AAC at amino acid position 26.…”
mentioning
confidence: 99%
“…In general, sighted persons receive about 80% of their external information through vision (1]. In Japan, the number of the visually impaired is estimated to be approximately 360,000, of which about a half are totally blind [2]. The visually impaired must use other senses, such as hearing and touch, to replace the lost visual information.…”
Section: Introductionmentioning
confidence: 99%
“…It is reported, however, that 67% of the visually impaired are elderly people over 60 years of age [2]. It is also reported that the elderly exhibit the following tendencies [3].…”
Section: Introductionmentioning
confidence: 99%
“…LT has recently been reported to be involved in the pathogenesis of human demyelinating disease, multiple sclerosis (8). In addition, the anti-tumor effects of LT are also reported (3). Therefore, the attempt to introduce LT gene into the CNS of an experimental host will give great potential to contributing to further research work on the CNS diseases.…”
mentioning
confidence: 99%